(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Christian Values and Religious Freedom. Scholars rightly point out that, „throughout the Western world, the crisis that secularization brings to the traditional religious value system is most often perceived by religious discourse as a cause for concern or as a direct threat.” . It is acknowledged that „moral and religious values (intertwined, incidentally) are completely uncovered in the face of various forms of aggression. „The ‚eclipse of Christian values’ is thus perceived as a danger to the spiritual health of society. In the circumstances of the perpetuation of the attacks to which Christian values are exposed, such attitudes are timely and work to defend these values. Claiming respect for Christian values is absolutely necessary when the idea of reducing Christianity to ‚civil religion’ is being promoted. Religious freedom, as currently understood, is the condition in which individuals or groups are allowed, without restriction, to consent and, within certain limits, to express and act on the basis of their religious beliefs and identity in civil and political life, without coercive interference or sanctions imposed by outsiders, including the state.